Evaluation of soil-structure interaction effects from system identification of structures subject to forced vibration tests - Star, Lisa M.; Tileylioglu, Salih; Givens, Michael J.; Mylonakis, George; Stewart, Jonathan P. (Soil dynamics and earthquake engineering (1984), 2019)
We describe procedures to evaluate the dynamic properties of test structures subject to forced vibration testing. We seek modal vibration periods and damping ratios corresponding to the actual flexible-based response of the structure (incorporating the effects of compliance in the soil medium supporting the foundation) and similar attributes for a fixed-base condition in which only the flexibility of the structure is represented. Our approach consists of using suitable input and output time series with conventional parametric system identification procedures, and as such extends previously developed procedures for use with earthquake recordings. We verify the proposed approach and demonstrate its application using data from two test structures supported on shallow foundations that have been used in forced vibration tests and that have recorded earthquakes. The structures were tested with and without braces to modify their stiffness and were deployed at two sites with different soil conditions. We analyze the results to evaluate experimental period lengthening ratios and foundation damping. The results show (1) strong increases in period lengthening and foundation damping with the wave parameter (dimensionless ratio of structure-to-soil stiffness), (2) compatibility between modal properties from forced vibration testing and earthquake excitation, (3) soil nonlinearity increases period lengthening and modifies foundation damping in a manner that can be reasonably captured in predictive models using equivalent-linear soil properties compatible with a proposed shear strain index. •Procedures to evaluate dynamic properties of structures subject to forced vibration.•Flexible and fixed base response identified, used to evaluate inertial SSI effect.•Models of period lengthening and foundation damping reasonably predict response.•Show extension of analytical models for material and geometric nonlinearities.•Test data significantly adds to limited field data needed for SSI model validation.